Pergerakan Sampah Laut Yang Berasal Dari Sungai Di Perairan Selat Badung Dengan Pemodelan Numerik - Rifanti, Dewi Ayu; Hendrawan, I Gede; Mandhara Brasika, Ida Bagus (Journal of Marine Research and Technology; Vol 5 No 2 (2022): AUGUST 2022, 2022)
The issue of marine waste has become a global concern due to its impact on polluted biological systems. This occurs because, many individuals still believe that the ocean can handle waste on its own, so they toss trash into the waterway, ending th seas. There has been some research on marine flotsam and jetsam, but little research has been conducted on the distribution of marine debris and jetsam in the waters and along the coast of Badung Strait. This investigation seeks to determine the movement of marine debris and jetsam in the seas and along the coast of the Badung strait during the autumn season. The Limited Volume Coastal Sea Demonstrate (FVCOM) method induces 3D current patterns and particle dispersion patterns derived from 3D Lagrangian Molecule Simulations. As a result of the development of wind and currents, the way of flotsam and jetsam dispersion in the Badung Strait during the westerly season was primarily eastward. The pattern of flotsam and jetsam dispersion within the Badung Strait during the western season was primarily eastward due to the development of winds and currents. Additionally, marine flotsam and jetsam particles move along Badung Strait’s coastline to the coastline of Nusa Penida. In addition, Karangasem Rule, specifically the waters of Melanting Cape and Bugbug Cape, is home to an intriguing area for trash accumulation. This occurs because the shape of the shoreline, which is typically depressed, can trap flotsam and jetsam carried by water streams. In addition, the longer waste particles remain in the water, the more likely they are to be consumed by marine biota that cannot differentiate between their prey and marine waste, particularly filter-feeding marin animal